Scientific and Theoretical Basis of Physical Education and Sports Development in Uzbekistan (The Peerian Journal, 2023)
In this thesis, scientific conclusions about the role of physical education and sports as a social institution in society are presented, it is formed as one of the main means of socialization of the individual and the scientific and theoretical foundations of the development of the field are discussed